2021
DOI: 10.1002/cphc.202000952
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐driven Surface Instabilities of Tubular Chitosan Hydrogel

Abstract: Spatial structures break their symmetry under the influence of shear stress arising from fluid flow. Here, we present surface instabilities appearing on chitosan tubes when an acidic solution of chitosan with various molecular weight is injected into a pool of sodium hydroxide solution. At slow flow rates wrinkle‐to‐fold transition takes place along the direction of the flow yielding a banded structure. For greater injection rates we observe coexisting modes of wrinkles and folds which are stabilized to period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Patterns on the soft surface are monitored for a fixed alkaline concentration and injection rate when the ionic environment of the injecting CS sol is varied. An injection rate of Q = 1.01 mL min –1 was selected as a reference case because for the given alkaline concentration, coexisting modes of folds and wrinkles evolve on the pure CS tube, as shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Patterns on the soft surface are monitored for a fixed alkaline concentration and injection rate when the ionic environment of the injecting CS sol is varied. An injection rate of Q = 1.01 mL min –1 was selected as a reference case because for the given alkaline concentration, coexisting modes of folds and wrinkles evolve on the pure CS tube, as shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that the two bioactive compounds were effectively entrapped within the polymeric matrix with no effect on these physical proprieties of the produced microparticles. A liquid driven sol-gel transition by diffusion transport mechanism across the interface with selforganised surface deformation of chitosan hydrogels with wrinkle surface has been reported [41]. Here it is suggested that a rapid diffusion and evaporation of ethanol alongside water may have triggered a localized self-association of chitosan at the surface of the droplet since chitosan is insoluble in ethanol.…”
Section: Morphology and Size Of Microparticlesmentioning
confidence: 76%
“…These diagrams describe the response of the system (compression, tension, maximum curvature) as a function of a control parameter, for example, the imposed pressure difference. We use the results to identify a transition from unwrinkled to periodic wrinkled states and then to folded states similar to what is observed in spring-loaded linings or tubular chitosan hydrogel surfaces [7,25]. Fold states arise via secondary bifurcations from the wrinkled state as in the one-dimensional case.…”
Section: Introductionmentioning
confidence: 84%